2012
DOI: 10.2134/jeq2011.0222
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Isotope Study of Coal Utilization By-Products Interacting with Environmental Waters

Abstract: Sequential leaching experiments on coal utilization by-products (CUB) were coupled with chemical and strontium (Sr) isotopic analyses to better understand the infl uence of coal type and combustion processes on CUB properties and the release of elements during interaction with environmental waters during disposal. Class C fl y ash tended to release the highest quantity of minor and trace elements-including alkaline earth elements, sodium, chromium, copper, manganese, lead, titanium, and zinc-during sequential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Se, however, was elevated in both high-and low-SO 4 water types ( Figure 5). Similar to observations in the surface samples, high concentrations of B were not always associated with detectable levels of other CCR-related contaminants, and thus, some wells 17,22,28 The strong linear correlations support migration of water from the coal ash ponds as the source of high B and Sr levels and mixing with regional groundwater.…”
Section: Environmental Science and Technologysupporting
confidence: 69%
“…Se, however, was elevated in both high-and low-SO 4 water types ( Figure 5). Similar to observations in the surface samples, high concentrations of B were not always associated with detectable levels of other CCR-related contaminants, and thus, some wells 17,22,28 The strong linear correlations support migration of water from the coal ash ponds as the source of high B and Sr levels and mixing with regional groundwater.…”
Section: Environmental Science and Technologysupporting
confidence: 69%
“…Pennsylvania (Chapman et al, 2012), as well as leaching of U.S coals (Brubaker et al, 2013;Ruhl et al, 2014;Spivak-Birndorf et al, 2012), had a range of 0.70975 to 0.71910. Both leaching experiments of WV surface rocks and streams that discharged from valley fills in WV found that coal-bearing rocks have 87 Sr/ 86 Sr ratio ~0.7124 (Vengosh et al, 2013), which is similar to the values measured in groundwater in this study.…”
Section: Tracing the Source Of The Salinity And Hydrocarbons In Grounmentioning
confidence: 99%
“…A four-step aqueous sequential extraction procedure (Fig. 2) based on Stewart et al (2001) and Spivak-Birndorf et al (2012) DePaolo et al, 1983).…”
Section: Sequential Extractionmentioning
confidence: 99%